Legal requirements on the settlement of judicial disputes in the BRICS countries - Belikova, Ksenia Michailovna (2020)
This article aims to outline approaches to pre-trial dispute resolution in the establishment and development of Alternative Dispute Resolution (ADR) in BRICS countries (Brazil, Russia, India, China, and South Africa) in the form of voluntary settlement. with emphasis on building a system of alternative procedures. In this context, this study provides an understanding of the development vector of ADR in the BRICS format, based on relatively new legislation, which has not been adequately reflected in academic sources. Based on analytical reflections on information obtained from sources and literature indicated in the references, the article analyzes the provisions of the acts and normative documents of the BRICS countries, creating patterns of ADR development and the potential for its use from the position of principles legal. The results are presented in a set of legal prescriptions and scientific provisions within the current legislation regarding the field of research.